Special Education Teachers’ Knowledge of Using Assistive Technology with Students with Autism Spectrum Disorder - Alanazi, Abdullah (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The aim of this study was to explore teachers' knowledge of using assistive technology (AT) with students with Autism Spectrum disorder (ASD) based on their gender, years of teaching experience, level of education, grade level of instruction, and training. A sample of 312 teachers were collected in this study. Multiple Linear Regression was conducted for data analysis. Results indicated that trained teachers showed more knowledge of the using of AT in classrooms for students with ASD. Teachers who have more years of teaching experience reported more knowledge of using AT in classrooms for students with ASD. The results support a greater need for further studies using AT for students with ASD from stakeholders and decision makers perspectives in Saudi Arabia.